Students' satisfaction toward service quality in Admission and Records Department, Center for Foundation Studies, International Islamic University Malaysia - Raja Alias, Raja Noor Ashikin; Mohd Ali, Hairuddin (IIUM Press, 2011)
A brief study on customer satisfaction and service quality in A&R department of IIUM foundation studies. Using the SERVQUAL framework, the study seeks to answer three research questions. Recommendation for further and future research were also suggested.